Controle da coleção em microfilme Relatórios ministeriais, 1a República ([publisher not identified], 1980)
Index to microfilm collection of "Relatórios" of various ministries of the Brazilian federal government during the period of the First Republic; filmed as part of a joint project of Plano Nacional de Microfilmagem de Periódicos Brasileiros, Fundação Nacional Pró-Memória, Biblioteca Nacional, and Latin American Microfilm Project.